Research Progress on Near-Infrared Small-Molecule Fluorescent Probes Responsive to γ-Glutamyl Transpeptidase - Luo, Mengyao; Ye, Changqing; Bao, Hongli (Synthesis)
γ-Glutamyl transferase (GGT) is a kind of cell membrane-bound enzyme which plays a key role in various physiological and pathological processes. The overexpression of GGT is highly connected to diseases including the liver disorders, cancers, and cardiovascular conditions. Near-infrared (NIR) fluorescent probes have emerged as powerful tools for detecting and imaging GGT activity due to their deep tissue penetration, minimal autofluorescence interference, and high signal-to-noise ratio. This review summarizes recent progress in GGT-activated NIR small-molecular fluorescent probes based on fluorophores including hemicyanine, dicyanomethylene derivatives, AIEgens, cyanine derivatives and others. The design strategies, structural features and their applications in cellular, tissue are highlighted. Despite significant improvements in sensitivity, selectivity, and biocompatibility, most probes operate in the first NIR window and still face challenges related to water solubility, targeting specificity, stability under complex physiological conditions, and clinical translation. Future efforts should be directed toward the development of NIR-II (1000–1700 nm) probes, optimization of their physicochemical properties, and the advancement of their applications in deep-tissue imaging, as well as in clinical diagnostics and therapeutics.